2012
DOI: 10.1590/s2237-60892012000400002
|View full text |Cite
|
Sign up to set email alerts
|

Common mental disorders in mothers vs. infant and obstetric outcomes: a review

Abstract: Transtornos mentais comuns em mães versus desfechos infantis e obstétricos: uma revisãoCommon mental disorders in mothers vs. infant and obstetric outcomes: a review Abstract Introduction: Pregnancy has been shown to increase women's vulnerability to mental disorders. Common mental disorders (CMDs) have been studied both in the general population and in pregnant vs. non-pregnant women. During pregnancy, CMDs have been considered a potential predictor of obstetric and infant outcomes. Methods: A search was cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 36 publications
(37 reference statements)
0
7
0
Order By: Relevance
“… 21 While this may be one of the reasons for the high rate of psychological morbidity among the participants during the pandemic, others have also observed that women living with HIV have an increased prevalence of most common mental health disorders 10–13 . Although studies have shown that common mental disorders like depression and anxiety are common in pregnancy, 16 , 29 , 30 there have been few studies among pregnant HIV-positive women. 31 , 32 We are not aware of any study that has compared depression and anxiety among HIV-positive and HIV-negative pregnant women in our environment.…”
Section: Discussionmentioning
confidence: 99%
“… 21 While this may be one of the reasons for the high rate of psychological morbidity among the participants during the pandemic, others have also observed that women living with HIV have an increased prevalence of most common mental health disorders 10–13 . Although studies have shown that common mental disorders like depression and anxiety are common in pregnancy, 16 , 29 , 30 there have been few studies among pregnant HIV-positive women. 31 , 32 We are not aware of any study that has compared depression and anxiety among HIV-positive and HIV-negative pregnant women in our environment.…”
Section: Discussionmentioning
confidence: 99%
“…A review on focusing on CMDs in mothers versus infant and obstetric outcomes in 2012 reported CMD varying from 12 to 43% during pregnancy both in LMICs and in high-income countries though economic conditions increase women's vulnerability in LMICs (12).…”
Section: Maternal Mental Illness Affects Child Health and May Increasmentioning
confidence: 99%
“…The rationale for investigating CMD in pregnant women is that, because pregnancy is a period of physiological mal-adjustment, psychological and social factors may impose vulnerability to develop mental distress (12). Little is known about the prevalence and risk factors of CMDS in pregnant women in LMICs including Ethiopia.…”
Section: Maternal Mental Illness Affects Child Health and May Increasmentioning
confidence: 99%
See 1 more Smart Citation
“…It is based, by the unexpected fall of these hormones in the puerperal period, a theory on the etiology of the postpartum depression. 34,37 Oxytocin, also known as the "love hormone," is known for the promotion of uterine contractions and also acts on breastfeeding and the sensation of pleasure during sexual intercourse. It is noted that low levels of oxytocin can cause anxiety, maternal aggression and damage to social cognition.…”
Section:  Approached Disordersmentioning
confidence: 99%